Synergistic carbon nanostructures for high energy density lithium metal capacitors - Ganesh, Gayathry; Natarajan, Karthic; Deivendran, Gokul Raj; Izan Izwan, Misnon; Yang, Chunchen; Jose, Rajan (John Wiley and Sons Inc, 2025)
Lithium metal capacitors (LMCs) are analogues to lithium metal batteries (LMBs), sharing similar anode (lithium) but differing cathodes (porous carbon and transition metal compounds, respectively) and storage mechanisms. Porous carbon cathode of LMCs can be synthesized from carbon-negative sustainable sources, but the transition metal compounds in LMBs leave significantly high carbon and material footprints. Herein, ultrahigh specific energy LMCs are demonstrated using biomass-derived commercial carbon modified with carbon quantum dots (CDs) and single-walled carbon nanotubes (SWCNTs) that outperformed the theoretical capacity of several LMB cathodes. The optimized LMC delivered a specific capacitance of ≈250 F·g−1 (specific capacity ≈194 mAh·g−1), specific energy of ≈545 Wh·kg−1, and specific power of ≈11.2 kW·kg−1 with an order of magnitude higher cycling stability than LMBs. Additionally, the impact of lithium inventory on the performance of the device is investigated, which delivered a specific energy of ≈522 Wh·kg−1. Unlike the high self-discharge exhibited by carbonaceous cathodes in electrochemical capacitors, the self-discharge in the present LMCs is negligible over an incubation of 7 days. A pouch cell with a mass loading similar to the commercial devices is fabricated to demonstrate its deployability, which retained 95% of its initial capacitance over 500 cycles.